FROM EDUCATION TO LABOUR MARKET - Mospan, Natalia (Continuing Professional Education: Theory and Practice, 2019)
Teachers play a crucial role in supporting the learning experience of young people and adult learners. Their profession has a vital role in advancing human potential and shaping future generations. Therefore, the European Union views the role of teachers and their career development as key priorities.In the European Union much attention is paid to the problems of graduates’ transition from higher education to the labour market. But this process is not controlled in Ukraine.This article presents an analysis of labour market outcomes for Ukrainian graduates with teacher higher education, which is based on the teacher education graduates survey 2015, especially the entry of young people into the labour market. The study of statistic data of graduates of pedagogical departments of leading Ukrainian universitiesmade it possible to identify employment sectors of graduates and their labor market status in 2015. Besides, the present study investigates the issues of the source of funding of education, transition period, graduates’ employment mechanisms and employment sectors in the labour market. The evidence presented in this article indicates that teacher higher education is effective enough in helping the transition from education to work. Teacher education graduates in Ukraine with national teacher higher education system, with a close connection between school- and the work-based components, are much more likely to be employed according to their qualification (education sector). They have a higher employment premium and face fewer difficulties in labour market integration. This is can be considered as an indication of benefits from a well-developed system – higher education institution – transition period – labour market. The empirical findings in this article should contribute to understanding a current state of labour market outcomes for teacher education graduates in Ukraine.